Enrichment and characterization of a bilge microbial consortium with oil in water-emulsions breaking ability for oily wastewater treatment - Corti-Monzón, Georgina (2020)
Oily bilge wastewater is one of the main sources of hydrocarbons pollution in marine environments due to accidental or clandestine discharges. The main technical challenge for its effective treatment is the presence of stable oil-in-water (O/W) emulsions. In this work we are reporting an enriched microbial consortium from bilge wastewater with remarkable ability to demulsify oil in water emulsions. The consortium showed emulsion-breaking ratios up to 72.6% in the exponential growth phase, while the values range from 11.9 to 8.5% in stationary phase. A positive association was observed between demulsifying ability and microbial adhesion to hydrocarbons, as well as between cell concentration and demulsifying ability. Also, an interesting ability to demulsify under different temperatures, conditions of agitation, and bilge emulsions from different vessels was observed. The Bacterial and Archaeal composition was analyzed by 16S rRNA gene amplicon lllumina sequencing analyses, revealing an assemblage composed of bacterial types highly related to well characterized bacterial isolates and also to non-yet cultured bacterial types previously detected in marine and sediment samples. Hydrocarbonoclastic microbial types such as Marinobacter, Flavobacteriaceae, Alcanivorax and Gammaproteobacteria PYR10d3 were found in high relative abundance (27.0%– 11.1%) and types of marine oligotrophs and surfactant degraders such as Thallasospira, Parvibaculum, Novospirillum, Shewanella algae, and Opitutae were in a group of middle predominance (1.7–3.5%). The microbial consortium reported has promising potential for the biological demulsification of bilge wastewater and other oily wastewaters.